Preoperative and Postoperative Sitting Radiographs for Adult Spinal Deformity Surgery: Upper Instrumented Vertebra Selection Using Sitting C2 Plumb Line Distance to Prevent Proximal Junctional Kyphosis. Issue 15 (1st August 2020) - Yoshida, Go; Ushirozako, Hiroki; Hasegawa, Tomohiko; Yamato, Yu; Kobayashi, Sho; Yasuda, Tatsuya; Banno, Tomohiro; Arima, Hideyuki; Oe, Shin; Mihara, Yuki; Ide, Koichiro; Watanabe, Yuh; et al.
Abstract : Study Design: Case-control study from a continuous series. Objectives: To study the impact of perioperative sitting radiographs in adult spinal deformity (ASD) patients and determine whether proximal junctional kyphosis (PJK) can be prevented using preoperative sitting radiograph. Summary of Background Data: Radiographic analysis of ASD comprises standing whole-spine radiography which cannot evaluate the relaxed posture without head-to-foot compensation. Methods: Preoperative and postoperative whole-spine standing and sitting radiographs and proximal mechanical complications in surgically treated spinal disorders with a minimum of 1-year follow-up were studied. Whole-spinal alignment was defined by cervical lordosis (CL), sagittal vertical axis (SVA), T1 slope (T1S), thoracic kyphosis (TK), lumbar lordosis (LL), pelvic incidence (PI), pelvic tilt (PT), sacral slope (SS), and level of kyphotic apex (KA). Proximal mechanical complication was described as a PJK (proximal junctional angle >20°) or reoperation due to proximal junctional failure. Results: Surgically treated 113 patients were prospectively investigated. Patients were divided into either the ASD (thoracic to ilium posterior corrective fusion), or non-ASD groups. In the ASD group, 10 patients had postoperative PJK, and three revision surgeries were carried out due to PJF with neurological deficit. Comparing standing with sitting positions, CL, TK, and PT became larger, SVA became frontal, LL and SS became smaller, and KA became caudal particularly in the ASD group. Logistic regression analysis demonstrated that the most influenced plumb line for PJK was the upper instrumented vertebra (UIV) to C2 plumb line distance, with a cutoff value of 115 mm for predicting PJK. Conclusion: Our findings highlight the usefulness of sitting spinal alignment evaluation, particularly in ASD patients, with maximum effort of thoracic spine and lower extremity compensation at standing. Mechanical complications such as PJK could be predicted using the distance from the planned UIV to the C2 plumb line in preoperative sitting radiographs. Level of Evidence: 3 Abstract : ASD patients had larger SVA, TK, and PT compared with non-ASD patients in sitting radiographs due to a large reduction in compensation in the sitting position. Surgical strategies for ASD should consider preoperative sitting radiograph to prevent PJK, taking the distance between UIV to C2 plumb line distance into account.